2020
DOI: 10.21070/perisai.v4i1.228
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Sharia and Conventional Shares’ System at Indonesia Stock Exchange

Abstract: There are lots of alternative investing. It is started from investment real assets, securities, from conventional and manifold sharia. Islamic Capital market and conventional have some type securities which have different risk level of risks. A stock is one of securities among other securities that have the high level of risk. One of the risks that exists in the stock is fluctuations price, it is commonly called as volatility. The aim of this research is to identifiy the risk of sharia stock and conventional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…In contrast to (Ahmed, 2020) explaining that there is no strong evidence of the existence of a positive risk-return tradeoff in Bitcoin markets, meaning that high risk does not necessarily generate high returns. Research on sharia stocks, the majority concluded that the performance of conventional stocks is better than sharia stocks (Abu-Alkheil et al, 2020;Hersugondo et al, 2020;Suryadi et al, 2021).…”
Section: Returns and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to (Ahmed, 2020) explaining that there is no strong evidence of the existence of a positive risk-return tradeoff in Bitcoin markets, meaning that high risk does not necessarily generate high returns. Research on sharia stocks, the majority concluded that the performance of conventional stocks is better than sharia stocks (Abu-Alkheil et al, 2020;Hersugondo et al, 2020;Suryadi et al, 2021).…”
Section: Returns and Risksmentioning
confidence: 99%
“…Among them are focusing on cryptocurrency instruments that cryptocurrency promises high returns but the risk is also very high (Borri, 2019;Guo & Li, 2017;Xu et al, 2021;Zhang et al, 2021), contrary to research from (Ahmed, 2020) which explains there is no strong evidence of the existence of a positive risk-return trade-off in Bitcoin markets, meaning that high risk does not necessarily generate high returns. On the other hand, research on the stock market also focuses on one investment instrument, research from (Hersugondo et al, 2020;Suryadi et al, 2021) states that the volatility of the conventional stock market is higher compared to the sharia stock market, indicating higher risk on conventional stocks. In line with research (Abu-Alkheil et al, 2020) shows that sharia stocks are less sensitive to average market movements compared to conventional stocks.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian sebelumnya banyak yang membandingkan risk dan return pada saham Syariah dengan konvensional seperti penelitian yang di lakukan oleh (Abbes, 2012) menyatakan bahwa tidak terdapat perbedaan yang signifikan antara risk dan return saham Syariah dan konvensional. Penelitian lainnya (Jawadi et al, 2014), (Tas et al, 2016), (Hersugondo et al, 2020) menghasilkan kesimpulan saham Syariah lebih efisien dibandingkan saham konvensional. Hasil penelitian yang berbeda dengan (SURYADI et al, 2021) berdasarkan data yang dihasilkan dan diolah selama Januari 2017 hingga Juli 2019, tingkat pengembalian saham konvensional lebih besar dibandingkan tingkat pengembalian saham Syariah pada Mei 2019.…”
Section: Hasil Dan Pembahasan 31 Hasil Penelitianunclassified
“…One of the critical decisions faced by investors in choosing an investment is the decision to invest with the sharia and conventional system. As it is stated by Hersugondo et al (2020), the decision to invest in the capital market is caused by three factors: firstly, the capital market is an alternative way of funding besides banking. Secondly, the capital market allows investors to have various investment options that suit their risk preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, investment in securities has high liquidity to enable efficient allocation of funds. Two things are essential for investors to invest in stocks, i.e., returns and risks (Hersugondo et al, 2020). Many investment options include savings, mutual funds, bonds, supplies, etc.…”
Section: Introductionmentioning
confidence: 99%